Przesłanki stanowienia norm bez sankcji - Jabłońska-Bonca, Jolanta (Wydział Prawa i Administracji UAM, 1984)
The article focuses of the problem of leges imperfectae. The authoress presents some probable reasons for providing norms of that type in the context of knowledge of the theory of organization and sociotechnics, concentrating her attention on discussing norms delimiting tasks of state administration They establish a duty to realize specific goals or to act in a given direction. Their importance is presently increasing, what is related to the expanding legal regulation in a sphere of administration and economy. A substantial amount of those norms is not sanctioned in legal provisions. In search of grounds to provide norms of that type, the authoress examines conditions of operation for a given norm, characteristic features of addressees, properties of regulation subject and other circumstancies in which a law making decision is being made.
Premises for providing norms without sanction